Potential Use and Challenges of Constructed Wetlands for Wastewater Treatment and Conservation in Game Lodges and Resorts in Kenya - Richard O. B. Makopondo; Laban K. Rotich; Cynthia G. Kamau (The Scientific World Journal)
Constructed wetlands are cost-effective wastewater treatment alternatives that receive worldwide acceptance. For the Kenyan hospitality industry, in particular, constructed wetlands (CWs) provide opportunities for wastewater reuse and recovery of resources, as well as improvements in local environmental conditions. Hospitality establishments produce large volumes of wastewater that is sometimes discharged to the environment without being treated. This is not only harmful to communities living downstream of these rivers but also to the flora and fauna which are the main attraction for most who visit these lodges. This study used qualitative methods to collect and analyze published official government documents, peer-reviewed research articles, and professional reports including leading international and Kenyan case studies to explore how constructed wetlands can be effectively used in game lodges and resorts situated in arid and remote areas of Kenya. The study investigated wastewater management systems adopted by remote game lodges and resorts in Kenya and the potential role, as well as the challenges to adopting constructed wetland (CW) technology. The results indicated that hotels, game lodges, and resorts both internationally and locally are adopting different types of CWs including surface and subsurface flow as alternative nature-oriented wastewater management systems. The study identified opportunities in the use of CWs as a wastewater management and conservation strategy. The results suggest that there are potential challenges which include inadequate expertise and technical support; low volume of discharge during off-seasons; limited space or land; and the attitude of hospitality managers towards constructed wetlands. Based on these preliminary findings, one may conclude that game lodges, ecolodges, and resorts in remote areas are prime candidates for constructed wetland establishment. The study makes specific recommendations with implications for policy and practice to promote sustainable hospitality operations and environmental conservation. It is suggested that future studies test the efficacy and efficiency of CW technology as wastewater management systems in the Kenyan wilderness areas including national parks, game reserves, and forests.